Improving Indonesian Learning Results In Suggestion Sentences With Guided Discovery Learning Model - Lestari, Windri Indah (Universitas Sebelas Maret, 2022)
The purpose of this research was to improve the learning outcomes of students in the Indonesian language lesson, Suggestion Sentence Material in grade III elementary schools with the guided discovery learning model. The research conducted was Classroom Action Research (PTK). The sequence of research activities includes 4 stages including: (1) planning, (2) implementation, (3) observation, and (4) reflection. The learning outcomes of students in the first cycle after carrying out the post test were 25%. In the second cycle students who completed after carrying out the post test were 83%. In the third cycle students who completed after carrying out the post test were 92%. The results of this study indicate that: (1) the application of the guided discovery learning model is in accordance with the material, where the steps of the guided discovery learning model include: a) introduction, b) repetition, c) overview, d) investigation, e) representation, f ) discussion, g) findings, h) application, i) conclusions, and j) assessment. (2) learning through the guided discovery learning model has increased in each cycle.